Consolos de concreto moldados em duas etapas: influência do tratamento da interface e da adição de fibras de aço - Oliveira, Edilene Muniz de (2012)
Concrete corbels are among the most used components to connect precast elements. Series production is often prejudiced by the necessity of making corbels in different positions in precast elements. To reduce this obstacle and rationalize the production, execution of concrete corbels cast in two stages can be a good alternative. The researche reported here intended to evaluate different procedures of making concrete corbels cast in two stages, being column cast firstly and, after removing formwork, corbels can be cast. Concrete corbels with and without steel fibers, both with horizontal stirrups and with steel fibers replacing it, with varying the treatment of joint and the shape of the connect the main steel bars to the column were analyzed. To do so, experimental and analytical analyses of concrete corbels cast monolithically and in two distinct phases were carried out. In the tests, the strength, vertical and horizontal displacements in relation to the column, the opening of cracks and strains of main steel and horizontal stirrups were determined. From these tests it was observed that the ultimate strength of monolithic corbels increased significantly when steel fibers were added to concrete, even when they replaced the horizontal stirrups, but this increase did not occur in concrete corbels cast in two stages. However, it was observed that steel fibers could replace the horizontal stirrups without damage to the bearing capacity. Besides, the presence of horizontal stirrups increased the ultimate strength of the concrete corbels without steel fibers cast in two stages. It was also observed that the opening of the joint between the corbel and the column was also influenced by the presence of horizontal stirrups for concrete corbels cast in two stages and monolithic concrete corbels. In the other hand, steel fibers added to the concrete did not affect the opening of the joint corbel-column of corbel cast in two stages, but substantially reduced this opening in monolithic corbels. Finally, it was observed that the treatment of the interface had little significance in the ultimate strength of the concrete corbels cast in two stages, but it influenced the opening of this interface, although only in concrete corbels with horizontal stirrups.